Prepper's survival medicine handbook a life-saving collection of emergency procedures from U.S. Army field manuals - Finazzo, Scott (Ulysses Press, 2016)
A handy guide to field-tested medical procedures specifically designed for critical times when no doctor is available. When disaster strikes and no doctors are available, you'll have to rely on your own medical knowledge to survive. Prepper's Survival Medicine Handbook goes beyond basic first aid to teach you military-tested methods for treating life-threatening medical conditions, including: Gunshot wounds; Third degree burns; Radiation exposure; Broken bones; Ruptured arteries; Severed limbs; Poisonous snakebites; Anaphylactic shock. The author, an emergency responder, details step-by-step treatment for everything from hypothermia and heat stroke to seizures and cardiac emergencies. Using information from actual military field manuals, this book provides everything you need to keep you and your loved ones safe when there's nowhere else to turn.